Smart Contact Lenses for Biosensing Applications - Ma, Xin; Ahadian, Samad; Liu, Song; Zhang, Jingwen; Liu, Shengnan; Cao, Teng; Lin, Wenbin; Wu, Dong; Barros, Natan Roberto de [UNESP]; Zare, Mohammad Reza; Diltemiz, Sibel Emir; Jucaud, Vadim; et al. (Wiley-Blackwell, 2021)
Smart contact lenses have emerged as novel wearable devices. Due to their multifunctional biosensing capabilities and highly integrated performance, they provide a great platform for the diagnosis of eye diseases and the delivery of drugs. Herein, a brief history of the development of contact lenses is given. Then, the state-of-the-art design and fabrication of smart contact lenses for biomedical applications, including contact lens materials, fabrication technologies, and integration, are presented. Furthermore, biosensors implemented in contact lenses to measure lactic acid, glucose, intraocular pressure, and other key metabolites in tears are highlighted. Applications of smart contact lenses in drug delivery are also described. These unique features make smart contact lenses promising diagnostic and treatment devices. Challenges and future opportunities for further applications of smart contact lenses in biomedicine are also discussed.
Keywords: biosensors; diagnoses; drug deliveries; microfluidics; smart contact lenses